Pengaruh Variasi Konsentrasi Bahan Tambah Limbah Tetes Tebu Terhadap Kuat Tekan Beton - Hartanto, Taufik Dwi Tyas, Basuki, S.T, M.T (2017)
Concrete is an artificial rock composed of hardening of a particular mixture of water, cement and aggregates. Concrete material which is not foreign in the field of civil engineering, for almost every building using concrete as the main structure and a good complement to the bridges, waterworks, and buildings. Because concrete is a composite material, the quality of the concrete depends on the respective constituent materials (Tjokrodimuljo, K, 1996). Materials added molasses is used as a material for environmentally friendly concrete technology will be examined in this study. This study aimed to determine the effect of molasses original with variation 0.00%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35% and molasses whose concentration changed cane Molasses: water (1: 0.5) with a percentage of 0.40%, 0.45%, 0.50%, 0.55%, 0.60% of the use of cement and cement water factor determined the same in all variations, amounting 0.4. Sample used cylindrical (d = 15cm; h = 30cm), the quality of concrete was planned 20 MPa. Number of samples 66, each comprising six sample variation. In testing the slump increased the value of the slump is directly proportional to the increased variety of molasses thus improving workability. Compressive strength test results showed an increase in the maximum compressive strength at ages of 7 and 28 days with a rate of 0.20% by weight of cement molasses is 22.07 MPa and 28.11 MPa, and a compressive strength lowest in molasses with a rate variations 0 , 60% ie 16.13 MPa and 21.50 MPa. Increased strength of concrete age of 7 days to 28 days on the test results is higher than the strength of concrete reinforcement theoretically based PBI 1971.NI-2, this happens because the cement used is a cement-type PCC (Portland Composite Cemen) so that the binding cement initial increase, but as a percentage of the addition of molasses to each mixing concrete, compressive strength of the concrete without the added material molasses decreased. Molasses can be classified on the added material retarder, as a percentage of the addition of molasses to the normal thresholds can serve to slow the hardening of concrete, inhibiting the rise in temperature, as well as making cement have more time to process hydratious so that concrete is more dense. and when the percentage of addition of molasses levels exceed normal limits will result in excessive deceleration even lead to hardened concrete can not thus lowering the strength of the concrete.